2002
DOI: 10.1034/j.1600-0714.2002.310102.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral candidiasis as a clinical marker related to viral load, CD4 lymphocyte count and CD4 lymphocyte percentage in HIV‐infected patients

Abstract: These findings suggest that oral candidiasis could be a useful clinical marker of patients with high viral load. In view of these results, emphasis should be placed on the importance of systematic examination of the oral cavity in all medical follow-up examinations of HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
2
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 36 publications
9
57
2
18
Order By: Relevance
“…[30][31][32][33] However, this is consistent with the findings reported by other investigators. 29,34 We also observed a higher prevalence of PC in males than in females (17.7% and 10.6%, respectively; P <0.05). Patients with OC had 1.96 times higher chance of having their CD4 counts ≤200 than patients without OC.…”
Section: Discussionsupporting
confidence: 49%
“…[30][31][32][33] However, this is consistent with the findings reported by other investigators. 29,34 We also observed a higher prevalence of PC in males than in females (17.7% and 10.6%, respectively; P <0.05). Patients with OC had 1.96 times higher chance of having their CD4 counts ≤200 than patients without OC.…”
Section: Discussionsupporting
confidence: 49%
“…Candida carriage lebih sering pada wanita, atau orang-orang dengan golongan darah O, diet tinggi karbohidrat, xerostomia, pengguna antimikroba spektrum luas (contoh: tetrasiklin), pemakai protesa gigi, perokok, kondisi immunocompromised (penyakit HIV, sindrom Down, malnutrisi, atau diabetes), dan pasien yang dirawat di rumah sakit. 2,4,5,6 Berbagai literatur telah banyak melaporkan hasil penelitian maupun laporan kasus terkait oral candidiasis, tetapi penelitian terutama dalam bidang Ilmu Penyakit Mulut di Indonesia masih Majalah Kedokteran Gigi Indonesia. April 2017; 3(1): 23 -28 ISSN 2460-0164 (print) ISSN 2442-2576 (online) belum banyak, sehingga penting untuk melakukan penelitian ini sebagai upaya menambah data awal mengenai prevalensi kandidiasis dan memberikan informasi yang berguna untuk peningkatan kesehatan masyarakat khususnya di bidang Ilmu Penyakit Mulut dan kesehatan mulut secara umum.…”
Section: Pendahuluanunclassified
“…Perawatan kandidiasis rongga mulut memerlukan identi kasi yang tepat, baik faktor predisposisi maupun kondisi sistemik yang menyebabkan kandidiasis. 2,4,5,18 . Sekitar 40,2% penderita candida pada penelitian ini terdapat riwayat penggunaan antibiotik dan obatabatan secara sistemik hal tersebut sesuai dengan literature yang menyebutkan bahwa kandidiasis biasanya berhubungan dengan terapi steroid jangka panjang, antibiotik spectrum luas, dan kondisi sitemik seperti de siensi nutrisi, diabetes mellitus, anemia/leukemia, dan HIV/AIDS.…”
Section: Pembahasanunclassified
“…Prevalence of oral lesions has been shown to be significantly higher in individuals with a CD4+ count less than 200 cells/mm 3 and a viral load greater than 3000 copies/mL (Bravo et al, 2006;Greenspan et al, 2000;Tappuni & Fleming, 2001). The importance of oral lesions as clinical indicators of HIV infections and markers of clinical progression to AIDS has been demonstrated in many studies that reported their association with CD4+ depletion and high viral load (Bravo et al, 2006;Campo et al, 2002;Chattopadhyay et al, 2005;Glick et al, 1994;Greenspan et al, 2000;Patton, 2000;Ramírez-Amador et al, 2003;Shiboski et al, 2001). A comprehensive review of epidemiologic studies on HIV-related oral lesions reported from developed and developing countries over more than a decade, encompassing the pre-HAART and early-HAART period from 1986 to 2000, revealed oral candidiasis as the most common lesion found in all ages across the world (Patton et al, 2002).…”
Section: Epidemiology Of Hiv-associated Oral Manifestationsmentioning
confidence: 99%